Engineering protein polymers of ultrahigh molecular weight via supramolecular polymerization: towards mimicking the giant muscle protein titin. Issue 40 (27th August 2019) - Wang, Ruidi; Li, Jiayu; Li, Xiumei; Guo, Jin; Liu, Junqiu; Li, Hongbin
Abstract : Utilizing protein fragment reconstitution of a small protein GB1, we developed an efficient, supramolecular polymerization strategy to engineer protein polymers with ultrahigh molecular weight that mimic the giant muscle protein titin. Abstract : The giant muscle protein titin is the largest protein in cells and responsible for the passive elasticity of muscles. Titin, made of hundreds of individually folded globular domains, is a protein polymer with folded globular domains as its macromonomers. Due to titin's ultrahigh molecular weight, it has been challenging to engineer high molecular weight artificial protein polymers that mimic titin. Taking advantage of protein fragment reconstitution (PFR) of a small protein GB1, which can be reconstituted from its two split fragments GN and GC, here we report the development of an efficient, PFR-based supramolecular polymerization strategy to engineer protein polymers with ultrahigh molecular weight. We found that the engineered bifunctional protein macromonomers (GC -macromonomer-GN ) can undergo supramolecular polymerization, in a way similar to condensation polymerization, via the reconstitution of GN and GC to produce protein polymers with ultrahigh molecular weight (with an average molecular weight of 0.5 MDa). Such high molecular weight linear protein polymers closely mimic titin and provide protein polymer building blocks for the construction of biomaterials with improved physical and mechanical properties.